PENGARUH STRATEGI PERUSAHAAN TERHADAP FINANCIAL DISTRESS DENGAN DIVERSITAS DIREKSI SEBAGAI PEMODERASI (Studi pada Perusahaan Manufaktur Sub Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Gita Nurtiana, - (2021)
This study aims to see the effect of company's strategy on financial distress with moderation of board of directors' diversity in miscellaneous industrial sub-sector manufacturing companies in Indonesia periode 2015-2019. The research method used descriptive quantitative method and used panel data regression method to test the hypothesis which is processed by Eviews software on 25 companies selected based on purposive sampling technique. Secondary data was obtained from financial reports and annual reports for the period 2015-2019 from the IDX website, IDN Financial, and related companies. The research results prove that the company's strategy, both prospector and defender, has a significant influence on financial distress conditions. Diversity of abilitiess is able to moderate the effect of each strategy on financial distress conditions.